(untitled) (Indian Journal of Animal Production and Management, 2015)
A study was conducted to evaluate the production performance of crosses of Dahlem Red and local Hazra birds under intensive system of management. All chicks were brooded up to two months of age under deep litter system and thereafter transfer in cages and reared under similar management and environment for 72 weeks. There is significant variation in growth rate, age at sexual maturity, egg production, egg weight and mortality pattern of crosses compare to their parent birds. The crosses showed significantly (P<0.05) higher body weight, higher feed intake, better egg production rate, large egg size, higher egg weight and early sexual maturity than local Hazra birds under same system of management.